Interceptive orthodontic treatment need index for children in mixed dentition (study on 8-11 years old children at SDK Santo Yoseph 1 Denpasar): Indeks kebutuhan perawatan ortodontik interseptif pada anak dalam masa geligi pergantian (kajian pada anak usia 8–11 tahun di SDK Santo Yoseph 1 Denpasar) - Surwandi Walianto; Dwis Syahrul; Norman Hidajah; Yudha Rahina; Adiguna Putra Walianto (Makassar Dental Journal PDGI Makassar, 2021)
Objective: Mixed dentition is a stage where teeth of both deciduous and permanent dentition are seen from 6-12 years of age and most malocclusions make their appearance during this stage. Interceptive orthodontic treatment aims to recognize and elimina-te dental irregularities in the developing dentofacial complex to prevents malocclusion from worsening in the future. Intercepti-ve Orthodontic Treatment Need Index (I-OTNI) is an interceptive orthodontic treatment filtering instrument on children in mixed dentition. The aim of this study is to know the age of highest interceptive orthodontic treatment need on 8-11 years old child-ren in mixed dentition at SDK Santo Yoseph 1 Denpasar. Methods: Descriptive study with cross sectional approach, with sam-ples that match the inclusion criteria, conducted by intraoral examination for identification and fill in I-OCN form for classi-fication based on orthodontic treatment need. Result: 56.81% samples of 8 years old children, 46.34% samples of 9 years old children, 30.43% samples of 10 years old children, and 32.55% samples of 11 years old children need interceptive orthodontic treatment. Conclusion: Children at 8 years of age is the highest need of interceptive orthodontic treatment followed by 9 years of age. The 8 and 9-years-old children need more interceptive orthodontic treatment than 10 and 11-years old children that mea-sured using I-OTNI at SDK Santo Yoseph 1 Denpasar.